Assessment of Insulin Injection Practice of Nurses Working in a Tertiary Healthcare Center of Nepal - Shital Adhikari; Ramesh Sharma Poudel; Laxmi Rajbanshi; Shakti Shrestha (Hindawi Limited, 2018)
Introduction. Sound knowledge and good practice on insulin injection technique are essential for nurses in order to administer insulin correctly and to educate patients or their relatives adequately. This study aimed to assess the insulin injection practice through the use of insulin pen among nurses working in a tertiary healthcare center of Nepal. Materials and Methods. A cross-sectional descriptive study was conducted among 67 nurses working in one of the tertiary healthcare centers of Nepal. Demographic information and insulin injection practice of nurses through the use of insulin pen were assessed using self-administered questionnaire. Each correct practice was scored "1" and incorrect practice was scored "0." Results. The median (IQR) insulin injection practice score of nurses was 11 (9-12) out of 16. Thirty-seven (55.2%) nurses store insulin pen filled with insulin cartridge at room temperature while 57 (85.1%) nurses store unopened cartridge at refrigerator (2-8°C). The practice of hand washing and injection site cleaning was mentioned by 92.5% and 82.1% of the nurses, respectively. However, just over half of the nurses mix the premix (cloudy) insulin and prime insulin pen before each injection. Thirty-four (50.7%) nurses do not lift skin during injection and more than half of the nurses keep needle beneath the skin for less than 5 seconds after completely injecting the required dose of insulin. One out of ten nurses massage injection site after injecting insulin. Most of the nurses (86.6%) use single needle more than once and the median (IQR) frequency of needle reuse was 6 (3-12). Similarly, systematic site rotation was performed by 59 (88.1%) nurses and twenty (29.9%) nurses claim that they use single insulin pen for two different cartridges. Conclusion. The insulin injection practice of nurses assessed through the use of insulin pen was suboptimal and highlights the need for urgent educational intervention.